2013
DOI: 10.1590/s1808-16572013000400002
|View full text |Cite
|
Sign up to set email alerts
|

Detecção do vírus da Artrite Encefalite Caprina por nested PCR e nested RT-PCR em ovócitos e fluido uterino

Abstract: Caprine arthritis-encephalitis (CAE) is aninfectious disease caused by the caprine arthritis-encephalitis virus (CAEV), belonging to the lentivirus genus. The presence of the virus has been observed in the nervous system, respiratory tract and mammary gland, and also in the male and female genital tract. The objective of this study is to identify the virus in oocyte and uterine fluid of infected goats by molecular diagnostic techniques, in order to assess the possibility of CAEV transmission with reproduction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
10
0
3
Order By: Relevance
“…ANDRIOLI et al (2002) made viral isolation followed by nested-PCR and found that CAEV was present in the uterine fluid of positive goat nannies, corroborating with the findings of FIENI et al (2003), who also identified the presence of this virus in embryo washings. CAVALCANTE et al (2013) observed with reverse transcription polimerase chain reaction (RT-PCR) that six goats presented free viral particles in the uterine fluid, demonstrating the potential to transmit this pathogen, which explains the production of antibodies detected by WB in the newborn goat kids in this study.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…ANDRIOLI et al (2002) made viral isolation followed by nested-PCR and found that CAEV was present in the uterine fluid of positive goat nannies, corroborating with the findings of FIENI et al (2003), who also identified the presence of this virus in embryo washings. CAVALCANTE et al (2013) observed with reverse transcription polimerase chain reaction (RT-PCR) that six goats presented free viral particles in the uterine fluid, demonstrating the potential to transmit this pathogen, which explains the production of antibodies detected by WB in the newborn goat kids in this study.…”
Section: Resultsmentioning
confidence: 50%
“…However, viral particles may eventually pass through to the fetus, considering that they may be found in the reproductive tract (ANDRIOLI et al, 2002;CAVALCANTE et al, 2013). ANDRIOLI et al (2002) made viral isolation followed by nested-PCR and found that CAEV was present in the uterine fluid of positive goat nannies, corroborating with the findings of FIENI et al (2003), who also identified the presence of this virus in embryo washings.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…A fêmea "E" apresentou soroconversão a partir dos 30 dias pós-infecção à técnica de cELI-SA, e a partir dos 60 dias pós-infecção para IDGA. A fêmea "D" não apresentou nenhum resultado positivo durante o período monitorado, para as três técnicas diagnósticas, indicando que, naquele momento, a infecção estivesse localizada no sistema reprodutor conforme foi observado por Cavalcante et al (2013) ou uma possível transmissão para o embrião diretamente pelo sêmen infectado como sugerido por Ricarte et al 2010. As provas de imunodiagnóstico são dependentes da quantidade de anticorpos no organismo, que será afetada de acordo com o nível de replicação viral em cada animal (Tigre et al 2006), sendo observado menor tempo médio de soroconversão em rebanhos com maior prevalência (Peterhans et al 2004).…”
Section: Discussionunclassified
“…Recent data pointed that the nonsurgical uterine flushing seems to have an important role in the caprine arthritis encephalitis virus (CAEV) control programs [55]. Many studies revealed the presence of the virus in uterine flushing media after surgical technique [56][57][58][59][60][61]. However, no positive samples for CAEV were reported from flushing media and embryos recovered by nonsurgical procedure in the first centrifugation.…”
Section: Associated Sanitary Risks With Nonsurgical Embryo Transfer Imentioning
confidence: 99%